“To Enact a Postmodernism of Resistance”: The Transgressive Thought of bell hooks and the Interdisciplinarity of White-Supremacist Capitalist Patriarchy - Woodson, Hue (USAbroad – Journal of American History and Politics, 2023)
Through enacting what she refers to as “a postmodernism of resistance,” bell hooks works out and works through a methodology of transgressive thought, through a radical rhetoric of feminist ideology. When mouthed, this radical rhetoric is significantly inaugurated in part by the well-known text, Ain’t I A Woman, but is also launched in particular ways by hooks’s lesser-known 1983 dissertation on Toni Morrison’s The Bluest Eye and Sula. What becomes integral to hook’s transgressive thought is a critique of how black womanhood attends to keeping a hold on life, transgressively confronting the interdisciplinarity of white-supremacist, capitalist patriarchy.